Yield Optimization and Supercritical CO2 Extraction of Essential Oil from Jasmine Flower - Hesham Hussein Rassem; Abdurahman Hamid Nour; Rosli Mohammad Yunus; Yasmeen Hafiz Zaki; Hybat Salih Mohamed Abdlrhman (Indonesian Journal of Chemistry, 2019)
Supercritical fluid extraction (SFE) is an innovation that permits extraction of an extensive variety of different chemical composition from the plant grids. Extraction of essential oil from Jasmine flower was tentatively carried out using the supercritical CO2 technique. The effect of extraction parameters which include pressure (100–300 bar) and temperature (300–350 K) on the oil recovery was explored. The extraction process was optimized using the response surface methodology (RSM). At the SFE optimal conditions, the chemical compositions of the extracted oil were examined using gas chromatography-mass spectrometry (GC-MS) analysis. The obtained result reflected that the optimal yield of oil from Jasmine flower was 12.18% mg oil extracted/100 g dry flower, which was achieved through an SFE optimal conditions of pressure at 200 bar and extraction temperature at 325 K. A total number of six chemical compounds were tentatively identified in the Jasmine flower extracted oil at the optimal SFE conditions.